Liver’s influence on the brain through the action of bile acids - Yeo, Xin Yi; Tan, Li Yang; Chae, Woo Ri; Lee, Dong-Yup; Lee, Yong-An; Wuestefeld, Torsten; Jung, Sangyong (Frontiers in Neuroscience, 2023)
The liver partakes as a sensor and effector of peripheral metabolic changes and a regulator of systemic blood and nutrient circulation. As such, abnormalities arising from liver dysfunction can influence the brain in multiple ways, owing to direct and indirect bilateral communication between the liver and the brain. Interestingly, altered bile acid composition resulting from perturbed liver cholesterol metabolism influences systemic inflammatory responses, blood-brain barrier permeability, and neuron synaptic functions. Furthermore, bile acids produced by specific bacterial species may provide a causal link between dysregulated gut flora and neurodegenerative disease pathology through the gut-brain axis. This review will cover the role of bile acids—an often-overlooked category of active metabolites—in the development of neurological disorders associated with neurodegeneration. Further studies into bile acid signaling in the brain may provide insights into novel treatments against neurological disorders.